Validation of the persian version of health professionals communication skills scale - Hamid Sharif Nia; Seyedeh-Sakineh Salimi; Fahimeh Ghasemi Charati; Hamideh Azimi-Lolaty; Vida Shafipour (Wolters Kluwer Medknow Publications, 2022)
Background: The need for assessing health-care workers' communication skills is increasingly emphasized by researchers. Achieving such a goal requires the use of a reliable tool. The purpose of this study was to validate the Persian version of Health Professionals Communication Skills Scale (HP-CSS). Materials and Methods: For the present methodological study carried out from September 2016 to February 2017, 400 health workers were selected by convenience sampling from educational hospitals in Mazandaran province in Iran and they were asked to fill out the 18-item HP-CSS. All steps of the scale validity were performed. Exploratory and confirmatory factor analysis were used. The reliability of the tool was measured by internal consistency. Results: Two factors of care and verbal clarity with patients and respect for patients' rights, extracted by exploratory factor analysis, explained 47.38% of the variance. Content Validity Index (CVI) and Content Validity Ratio (CVR) of all items were higher than 0.79 and 0.49, respectively. Reliability coefficients of factors were found to be more than 0.70. Model's fitness indicators confirmed the construct of HP-CSS. Both factors had a convergent and divergent validity. Conclusions: This study showed that the Persian version of the communication skills scale has a two-dimensional construct and good psychometric properties; also, this scale was found to be useful for the purpose and context in which it will be used, that is, communication skills.